Self Pollination and Fruit Quality-Comparative Research of Sweet Cherry Cultivars - Thurzó, Sándor; Drén, Gábor; Racskó, József (Acta Agraria Debreceniensis, 2005)
In fruit production – among stone fruits – sweet cherry is considered to have great promise, but species of sweet cherry need improvement. Cherry plantations are advanced in years, therefore putting into operation high productivity plantations is an important field of research. Through clonal selection and cross-breeding, several new cherry species were created in the recent past in Hungary. Spread of these species is also important. In our factorial cherry production, we use high trunk trees and trees with large crowns. Intensive plantations are very few in number.Our goal is to study the morphological and physiological properties of new sweet cherry cultivars. The most important aim is to combine the productive area of foliage and the fruit quality. The present study shows the self pollination, fruit setting and fruit quality parameters.